1975
DOI: 10.1159/000117496
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia Susceptibility and HL-A Antigen

Abstract: The phenotype frequencies of HL-A specificities have been investigated in 47 chronic schizophrenics subdivided in an older and a younger group. The frequency of HL-A 9 was significantly increased in the psychotics as compared to a reference group of 1,263 healthy blood donors, pregnant women and potential kidney donors. Deviations in frequency were also found concerning W 19 and HL-A 5. As HL-A 9 was mainly found in the older group of schizophrenics, it is suggested that HL-A 9 might be associated to some form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…In psychiatry, significant associations have been described in connection with schizophrenia (6,10,27) and with affec tive psychoses by others (3,13,26) and also by our group (2). The results in the field of affective disorders are, however, still incon sistent.…”
mentioning
confidence: 62%
“…In psychiatry, significant associations have been described in connection with schizophrenia (6,10,27) and with affec tive psychoses by others (3,13,26) and also by our group (2). The results in the field of affective disorders are, however, still incon sistent.…”
mentioning
confidence: 62%
“…However, there is also significant heterogeneity across the studies (p = 0.015) so that in Japanese [Miyanaga et al, 1984] and in Swedish pa tients [Rudduck et al, 1984b] A9 was de creased compared with controls. This is somewhat surprising since in previous studies of schizophrenia as a whole both in Japan [/Isafcaet al, 1981] and Sweden [Eberhard et al, 1975] A9 was increased. Di agnostic differences may be responsible for the differences between centres.…”
Section: Hla Systemmentioning
confidence: 82%
“…Eberhard et al [1975] found a pronounced increase in A9 in older patients. It is possible to spec ulate that this was due to the inclusion of a high proportion of paranoid patients.…”
Section: Unfortunately Subsequent Investigatorsmentioning
confidence: 84%
“…Contrarily to investigations by other authors where a signifi cant decrease of HLA-A10 was found in schizo phrenic patients, a significant increase was found in our series. Our series did not include patients as old as those in the series by Eberhard et al (6), thus we were unable to divide our patients into comparable subgroups. Also, a subdivision into the classical schizophrenic diagnostic subgroups was not possible, partly because of the small number of patients in vestigated, and partly because most of the patients had been hospitalized for many years and had undergone different clinical phases of the disease.…”
Section: Commentsmentioning
confidence: 97%
“…In a larger series investigated later, the same group (10,11) found a significant ne gative association between HLA-A10 and schizophrenia in 146 patients. Eberhard et al (6) studied the distribution of HLA antigens in 47 chronic schizophrenic patients subdivided in an older and a younger group. They found a significant increase of HLA-A9 in the psychotics as compared to a large group of healthy individuals, the increase being most pronounced in an older subgroup (50 years or older).…”
mentioning
confidence: 99%